Varieties of platform unionism: a view from the Global South on workers’ power in the digital economy - Schmalz, Stefan (2023)
Nearly three decades ago, Manuel Castells declared the atomising effects of the new technologies of the ‘information age’ to presage the ‘end of labour’. There is little doubt that the labour movement worldwide is no longer the social force it was in the twentieth century. Much of the debate on the future of work and consequences for worker organisation, moreover, has focused on defensive struggles against the introduction of new technologies in the Global North. Technological change has also led, however, to struggles in the Global South. These ‘technological fixes’ have historically contributed to the ‘remaking’ of new working classes and related ‘offensive’ struggles, the latest of which is digitalisation and algorithmic management. In this primarily conceptual article, we adopt a power resources approach to an analysis of these changes, using as our basis, a project encompassing eight empirical case studies on recent labour organising in on-location platform economies of both the Global North and South. Analysis of food-delivery and private ride-hailing platforms in Argentina and Uganda, respectively, showed different varieties of platform unionism, with forms of worker organisation in the Global South tending to more autonomy and hybridity. In some cases, these self-organised worker collectives go beyond established forms of unionism in attempts to control the platform technologies. We conclude by suggesting that the experiments of platform workers with new forms of power and organisation, particularly in the Global South, are important to follow in the Global North.